2010
DOI: 10.1358/mf.2010.32.10.1533687
|View full text |Cite
|
Sign up to set email alerts
|

Preseasonal prophylactic treatment with antihistamines suppresses nasal symptoms and expression of histamine H1 receptor mRNA in the nasal mucosa of patients with pollinosis

Abstract: Administration of antihistamines 2-4 weeks before the pollen season showed a greater inhibitory effect on nasal allergy symptoms in patients with seasonal allergic rhinitis. However, the mechanism of slow-onset effects of preseasonal treatment with antihistamines remains unclear. Here, we investigated the effect of preseasonal prophylactic treatment with antihistamines on nasal symptoms and the expression of histamine H₁ receptor (H1R) mRNA of the nasal mucosa in patients with cedar pollen pollinosis. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…The strength of H1R signaling depends on the H1R expression level (8). Our recent studies have demonstrated that the level of H1R gene expression is strongly correlated with the severity of allergic symptoms in model rats and patients with pollinosis (9,10), and compounds that suppress H1R gene up-regulation alleviate allergic symptoms (11)(12)(13)(14)(15)(16). These findings suggest that the H1R gene is an allergy-sensitive gene, i.e.…”
mentioning
confidence: 99%
“…The strength of H1R signaling depends on the H1R expression level (8). Our recent studies have demonstrated that the level of H1R gene expression is strongly correlated with the severity of allergic symptoms in model rats and patients with pollinosis (9,10), and compounds that suppress H1R gene up-regulation alleviate allergic symptoms (11)(12)(13)(14)(15)(16). These findings suggest that the H1R gene is an allergy-sensitive gene, i.e.…”
mentioning
confidence: 99%
“…We have demonstrated that repeated pretreatment of antihistamines 1-5 weeks before provocation were more effective in suppressing both nasal symptoms and the expression of H1R mRNA in the nasal mucosa of the TDI-sensitized rats than their single administration [9]. Furthermore, we have shown that there was a significant correlation between the nasal symptoms and the expression level of H1R mRNA in patients with pollinosis [10].…”
Section: Discussionmentioning
confidence: 74%
“…Many studies have shown that activation of H1R by histamine is responsible for the symptoms of allergic rhinitis. Our recent data suggest that H1R gene is an allergic diseases-sensitive gene whose expression level affects severity of allergic symptoms [9,10], and compounds that suppress H1R gene expression should be good therapeutics [11][12][13]. The allergic reaction is also characterized by a disruption of Th1/Th2 balance toward a pronounced Th2 profile.…”
Section: Introductionmentioning
confidence: 99%
“…Histamine is a major chemical mediator of allergic reactions, and its action is mainly mediated through the activation of histamine H 1 receptor (H1R). 4 As a consequence, antihistamines are a widely employed first-line treatment for nasal symptoms of pollinosis. Recently, we reported that the H1R gene expression strongly correlated with the severity of allergic symptoms in toluene-2,4-diisocyanate (TDI)-sensitized rats, a commonly used allergy model, and patients with Japanese cedar pollinosis (3,4).…”
mentioning
confidence: 99%
“…4 As a consequence, antihistamines are a widely employed first-line treatment for nasal symptoms of pollinosis. Recently, we reported that the H1R gene expression strongly correlated with the severity of allergic symptoms in toluene-2,4-diisocyanate (TDI)-sensitized rats, a commonly used allergy model, and patients with Japanese cedar pollinosis (3,4). We also demonstrated that compounds that suppress up-regulation of H1R gene expression alleviate allergy symptoms (5)(6)(7)(8).…”
mentioning
confidence: 99%